Implementation of Corruption on Law Enforcement in the Criminal Justice System in Indonesia - Ariza Hasna; Nyoman Serikat Putra Jaya (Universitas Negeri Semarang, 2020)
The increase in criminal acts of corruption has brought disasters not only to the life of the nation and state in general, but also can cause various weaknesses in the lives of future generations. For this reason, strict, consistent and non-discriminatory law enforcement is needed for corruptors. However, law enforcement in the Criminal Justice System in Indonesia is still unable to carry out maximum law enforcement against corruption perpetrators, because there are still some weaknesses and problems, judging from the regulatory aspects there are still overlapping arrangements, the quality of the judiciary still needs to be improved because it has not been able to create justice in the public, the monitoring system of the performance of law enforcement officials related to corruption law enforcement still needs to be improved because it is not yet integrated, while the sanctions given are still considered to be not optimal so that it does not cause a deterrent effect to the perpetrators, so that in the future it is expected to change, reform and increase in Criminal Justice System in Indonesia.